Interactive Responses of Potato (Solanum tuberosum L.) Plants to Heat Stress and Infection With Potato Virus Y - Makarova, Svetlana; Makhotenko, Antonida; Spechenkova, Nadezhda; Love, Andrew J.; Kalinina, Natalia O.; Taliansky, Michael (Frontiers in Microbiology, 2018)
Potato (Solanum tuberosum) plants are exposed to diverse environmental stresses, which may modulate plant-pathogen interactions, and potentially cause further decreases in crop productivity. To provide new insights into interactive molecular responses to heat stress combined with virus infection in potato, we analysed expression of genes encoding pathogenesis-related (PR) proteins [markers of salicylic acid (SA)-mediated plant defence] and heat shock proteins (HSPs), in two potato cultivars that differ in tolerance to elevated temperatures and in susceptibility to potato virus Y (PVY). In plants of cv. Chicago (thermosensitive and PVY-susceptible), increased temperature reduced PR gene expression and this correlated with enhancement of PVY infection (virus accumulation and symptom production). In contrast, with cv. Gala (thermotolerant and PVY resistant), which displayed a greater increase in PR gene expression in response to PVY infection, temperature affected neither PR transcript levels nor virus accumulation. HSP genes were induced by elevated temperature in both cultivars but to higher levels in the thermotolerant (Gala) cultivar. PVY infection did not alter expression of HSP genes in the Gala cultivar (possibly because of the low level of virus accumulation) but did induce expression of HSP70 and HSP90 in the susceptible cultivar (Chicago). These findings suggest that responses to heat stress and PVY infection in potato have some common underlying mechanisms, which may be integrated in a specific consolidated network that controls plant sensitivity to multiple stresses in a cultivar-specific manner. We also found that the SA pre-treatment subverted the sensitive combined (heat and PVY) stress phenotype in Chicago, implicating SA as a key component of such a regulatory network..